Avaliação da densidade mineral óssea em mulheres na pós-menopausa tratadas de câncer e mama - Poloni, Priscila Ferreira [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Objective: To evaluate the risk factors for low bone mineral density (BMD) in postmenopausal breast cancer survivors compared to postmenopausal women without breast cancer. Methods: In this cross-sectional study, 112 breast cancer survivors were compared to 224 postmenopausal women (control), seeking healthcare at a University Hospital. Eligibility criteria included women with amenorrhea ≥ 12 months and age ≥ 45 years, treated for breast cancer and metastasis-free for at least five years. The control group consisted of women with amenorrhea ≥ 12 months, age ≥ 45 years and without breast cancer, matched by age and menopause status (in a proportion of 1:2 as sample calculation). The risk factors for low BMD (osteopenia and osteoporosis) were assessed by interviews. BMD was measured by dual energy X-ray absorptiometry (DEXA) at the lumbar spine (L1-L4) and femoral neck. Logistic regression model (odds ratio, OR) was used to identify factors associated with low BMD. Results: The mean (SD) age of breast cancer survivors was 61.3 (9.7) years, with a mean (SD) follow-up of 10.2 (3.9) years. Considering both sites assessed (spine and femoral neck), 77.7% of breast cancer survivors and 74.5% in the control group had low BMD (p = 0.302). The BMD at the lumbar spine did not differ between groups (p = 0.332). However, breast cancer survivors had a higher incidence of osteopenia (45.1%) and osteoporosis (22.3%) in the BMD at the femoral neck when compared to control (39.3% and 9.0%, respectively) (p = 0.0005). Univariate analyses, adjusted for age and time since menopause, revealed that chemotherapy (OR 6.90; CI 95% 5.57-9.77) was associated with higher risk for low BMD. Contrarily, regular physical exercise (OR 0.24; 95%CI 0.06-0.98) and body mass index (BMI) ≥ 30 kg/m2 (OR 0.09; 95% CI 0.02-0.37) reduced risk among breast cancer survivors. Smoking, use of hormone therapy, tamoxifen or anastrozole, history of fracture, rheumatoid ...

Objetivo: avaliar os fatores de risco para baixa densidade mineral óssea (DMO) em mulheres na pós-menopausa tratadas de câncer de mama comparadas a mulheres na pós-menopausa sem câncer de mama. Métodos: Realizou-se estudo transversal, com 112 mulheres tratadas de câncer de mama comparadas a 224 mulheres na pós-menopausa (controle), atendidas em Hospital Universitário. Foram incluídas no grupo de estudo mulheres com amenorréia ≥12 meses e idade ≥45 anos, tratadas de câncer de mama e livre de doença há pelo menos cinco anos. O grupo controle foi constituído de mulheres com amenorréia ≥12 meses e idade ≥45 anos sem câncer de mama, pareadas pela idade e tempo de menopausa, na proporção 1:2. Por meio de entrevista foram avaliados fatores de risco para baixa DMO (osteopenia e osteoporose). A DMO foi mensurada pela absorciometria de raios-X de dupla energia (DEXA) em coluna lombar (L1 a L4) e colo de fêmur. Regressão logística (odds ratio-OR) foi utilizada para identificar fatores associados à baixa DMO. Resultados: A média de idade das pacientes tratadas de câncer de mama foi de 61.3 ± 9.7 anos com tempo médio de seguimento de 10.2 ± 3.9 anos. Considerando ambos os sítios avaliados (coluna e colo de fêmur), 77.7% das mulheres tratadas de câncer de mama e 74.5% do grupo controle apresentavam baixa DMO (p=0.302). Na avaliação isolada da DMO em coluna lombar não houve diferença entre os grupos (p=0.332). Contudo, na DMO de colo de fêmur, as pacientes com câncer de mama apresentaram maior ocorrência de osteopenia (45.1%) e osteoporose (22.3%) quando comparadas ao controle (39.3% e 9.0%, respectivamente) (p=0.0005). Avaliando os fatores de risco para baixa DMO entre as mulheres com câncer de mama encontrou-se que quimioterapia prévia associou-se com aumento no risco (OR 6.90; IC 95% 5.57-9.77), enquanto que exercício físico regular (OR 0.24; IC 95% 0.06-0.98) e índice de massa corpórea (IMC) ≥ 30 kg/m2 ...
Keywords: Mamas - Cancer; Densidade óssea - Fatores de risco; Menopausa; Pós-menopausa; Osteoporose; Estudos transversais; Postmenopause; Breast - Cancer